1H and 13C NMR Study of Oligosuccinimide Prepared by Thermal Condensation and Evaluation of Its Scale Inhibition - Didi Prasetyo Benu; Muhamad Jalil Baari; Megawati Megawati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
The presence of scale is a serious problem in the petroleum industry, and some efforts should be made to control scale formation. Oligosuccinimide (OSI) is an oligomer with several repeating units of succinimide. The structure of the OSI main chain and end groups has never been comprehensively analyzed. Meanwhile, OSI is potentially a scale inhibitor due to chelating properties, high polarity, and high solubility. This study investigates the molecular structure of oligosuccinimide, focusing on the main chain and end groups. Synthesis was carried out by thermal condensation between maleic anhydride and ammonium carbonate using a 1H and 13C NMR spectroscope equipped with Distortionless Enhancement by Polarization Transfer 135, Heteronuclear Multiple Quantum Coherence, and Single Quantum Coherence. The NMR analysis results detected the presence of the main chain and several synthesized OSI end groups, such as the amino, succinimide, and maleimide end groups. However, the dicarboxylic acid end group and other irregular structures, as in polysuccinimide (various synthesis methods), were not identified. It confirmed that our thermal condensation method produced OSI with less irregular structures than previous methods. Evaluation of OSI as CaCO3 and CaSO4 scales inhibitor showed reasonably good performance in very small concentrations. The inhibition efficiency was 73.20% for the CaCO3 scale with 10 mg.L-1 and 55.29% for the CaSO4 scale with 10 mg.L-1 inhibitor concentration. Analysis of thermal stability informed OSI has good thermal stability because it started to be degraded at 353.38 °C.